Voltammetric studies of cobalt hexacyanoferrate formed on the titanium (IV) phosphate surface and its application to the determination of sulfite - Cumba, Loanda Raquel [UNESP]; Bicalho, Urquisa de Oliveira [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (My University, 2012)
Titanium (IV) Phosphate (TiPh) composite was prepared using a easily methodology of the synthesis. As a second step, TiPh was reacted with Cobalte (TiPhCo) and subsequent hexacyanoferrate was added (TiPhCoHCF). A preliminary characterization of the precursor and resulting materials was carried out using spectroscopic and voltammetric techniques. The electrochemical behaviour of the composite (TiPhCoHCF) was verified by means of a graphite paste electrode using cyclic voltammetry in a potential range of -0.2 to 1.0 V (vs Ag/AgCl). The cyclic voltammogram of the modified electrode containing TiPhCoHCF exhibited two redox couples. The first process (peak I) presented a formal potential (E Θ') = 0.37 V vs Ag/AgCl attributed to the redox process Co (II)/Co (III) and other more defined redox couple, (peak II), showed a E Θ' = 0.67 V vs Ag/AgCl which was attributed to the redox process [Fe (II)(CN) 6] /[Fe (III)(CN) 6]. The second redox couple exhibited an electrocatalytic activity towards the oxidation of sulfite. The titanium phosphate modified graphite paste electrode showed a linear response from 2.0×10 -3 to 1.0×10 -2 mol L -1 with the corresponding equation Y(μA) = 24.78 + 8.56 × 10 3 [Sulfite], and a correlation coefficient of r = 0.997. The method showed a detection limit of 6.51×10 -4 mol L -1 with a relative standard deviation of ± 5% (n = 3) and amperometric sensitivity of 9.19×10 -3 A mol L -1. © 2012 by ESG.
Keywords: Cobalte hexacyanoferrate; Graphite paste electrode; Titanium phosfate; Voltammetry